Brain activation induced by voluntary alcohol and saccharin drinking in rats assessed with manganese‐enhanced magnetic resonance imaging. (22nd August 2014) - Dudek, Mateusz; Abo‐Ramadan, Usama; Hermann, Derik; Brown, Matthew; Canals, Santiago; Sommer, Wolfgang H.; Hyytiä, Petri
Abstract: The neuroanatomical and neurochemical basis of alcohol reward has been studied extensively, but global alterations of neural activity in reward circuits during chronic alcohol use remain poorly described. Here, we measured brain activity changes produced by long‐term voluntary alcohol drinking in the alcohol‐preferring AA (Alko alcohol) rats using manganese‐enhanced magnetic resonance imaging (MEMRI). MEMRI is based on the ability of paramagnetic manganese ions to accumulate in excitable neurons and thereby enhance the T1‐weighted signal in activated brain areas. Following 6 weeks of voluntary alcohol drinking, AA rats were allowed to drink alcohol for an additional week, during which they were administered manganese chloride (MnCl2 ) with subcutaneous osmotic minipumps before MEMRI. A second group with an identical alcohol drinking history received MnCl2 during the abstinence week following alcohol drinking. For comparing alcohol with a natural reinforcer, MEMRI was also performed in saccharin‐drinking rats. A water‐drinking group receiving MnCl2 served as a control. We found that alcohol drinking increased brain activity extensively in cortical and subcortical areas, including the mesocorticolimbic and nigrostriatal dopamine pathways and their afferents. Remarkably similar activation maps were seen after saccharin ingestion. Particularly in the prelimbic cortex, ventral hippocampus and subthalamic nucleus, activation persisted into early abstinence. These data show that voluntary alcohol recruits an extensive network that includes the ascending dopamine systems and their afferent connections, and that this network is largely shared with saccharin reward. The regions displaying persistent alterations after alcohol drinking could participate in brain networks underlying alcohol seeking and relapse. Abstract : We measured brain activity changes produced by long‐term voluntary alcohol drinking in the alcohol‐preferring AA (Alko Alcohol) rats using manganese‐enhanced magnetic resonance imaging (MEMRI). We found that alcohol drinking increased brain activity extensively in cortical and subcortical areas, including the mesocorticolimbic and nigrostriatal dopamine pathways and their afferents. When rats with an identical alcohol drinking history were imaged during abstinence, persistent activity increases were seen particularly in the prelimbic cortex, striatum, and bed nucleus of the stria terminals.